Morphological and morphometric analysis of lung: A cadaveric study - Kanaujea, Savita; Arvind Kumar Pankaj; Dande, Kaweri; Sehra Jabeen; Navneet Kumar (Asian Journal of Medical Sciences, 2024)
Background: The lung is a respiratory organ in which steady development begins during the embryonic period at 0–7 weeks’ gestation and continues into early childhood. Cardiothoracic surgeries and procedures such as lobectomy, segmental resection of bronchoscopy, require a thorough knowledge of the anatomy of the lung. Study of length, fissures and lobes of the lung can guide the surgeons for the above procedures and help them to prevent undue complications during surgery. Many variations are noted by researchers till date in both the lungs in regards to length, breadth, fissures, and lobes. In the current study, we have also observed variations in fissures of lung. Aims and Objectives: To study the normal length, breadth, and thickness of both sides of lungs, variations in the length, breadth, and thickness of both sides of the lungs. To study the normal fissures, lobes and their variations, of both right and left lungs, and also to study the number of bronchi, pulmonary artery, and pulmonary vein. Materials and Methods: 50 Right and 50 left lungs were obtained from embalmed cadavers, used for dissection in the Department of Anatomy, King George’s Medical University, Lucknow, UP, by using measuring tape and measuring scale. Photography was done by a DSLR camera. Results: The left lung shows maximum variations in the hilum. Out of 50 left lungs, 6 showed the absence of oblique fissures, 2 lungs had 2 arteries, 2 lungs had 2 Veins, and 1 had 2 bronchi. Out of 50 right lungs, 2 lungs showed 2 arteries, 2 lungs had 2 veins, and 2 had 3 bronchi. Conclusion: Knowledge of normal measurements of both sides of the lungs and their variations may help cardiothoracic surgeons avoid complications during surgery and it may help radiologists resolve uncertain radiographic findings.